Government of Nagaland Draft Annual Plan 2003-2004 (Sectoral Plans) Volume-I - Planning Commission (Planning Commission, 2003)
Traditionally, All the tribes and villages in Nagaland practice slash and bum cultivation locally known as "Jhum". The Angami and Chakhesang tribes have on the other hand, developed a system of Wet Terraced Rice Cultivation (WTRC), which they practice alongside jhum cultivation, Modem scientific agriculture was introduced only in the 1960's. The impact has not been very appreciable, as most high external input technologies are not suitable for high altitudes and rainfed conditions. Moreover, traditionally Nagas did not cultivate any winter crop. Only in recent years, non-traditional winter crops such as wheat, barley and some pulses and oilseeds have been introduced. Now, it is gaining much popularity among the local farmers. Nagaland is traditionally a rice growing state. It occupies about 70% of the total area and constitutes about 75% of the total food grain production in the state. Besides, maize, millets, jobs tears, oilseeds, pulses, taro, yam, potato, sweet potato, fruits and many other vegetables are also grown.
Sectoral Plans
Government of Nagaland